Analyzing financial distress in the Indonesian Tourism Sector: A case study during the Covid-19 Pandemic - Maria Angelina Laurenzia Viviani Konten; Sari Yuniarti (Jurnal Penelitian, 2023)
Financial distress is a state of financial difficulty before the company finally experiences bankruptcy. The Covid-19 pandemic has had a significant negative impact on the financial state of various businesses in the Indonesian tourism industry. To prevent bankruptcy from occurring, it is important to assess the financial situation of affected companies to estimate financial distress. This research aims to analyze the effect of Return on Assets, Current Ratio and Debt to Total Asset Ratio on financial distress conditions in tourism sub-sector service companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The population in this research were all tourism sub-sector service companies listed on the Indonesia Stock Exchange that published their financial reports in 2019-2022. The sample was searched by purposive sampling and there were 32 companies and obtained 128 observation data consisting of 112 samples of financial distress companies and 16 samples of non-financial distress companies. Financial distress criteria are measured by interest coverage ratio. The statistical analysis used in this research is logistic regression. The results of this research indicate that partially Return on Assets and Debt to Total Asset Ratio affect Financial Distress, while Current Ratio has no effect on Financial Distress. Simultaneously Return on Assets, Current Ratio, and Debt to Total Asset Ratio affect Financial Distress.